Surgery for massive splenomegaly. Issue 1 (6th April 2017) - Lemaire, J; Rosière, A; Bertrand, C; Bihin, B; Donckier, J E; Michel, L A
Abstract: Background: Splenectomy for massive splenomegaly (spleen weight more than 1·5 kg) is commonly believed to be hazardous and to provide poor palliation. The aim of this cohort study was to investigate these issues and examine the many definitions of massive splenomegaly to see whether a better tool might be proposed for preoperative evaluation of these patients. Methods: Morbidity and long-term outcomes were assessed in consecutive patients. Relief of pressure–volume-related symptoms and sustainable independence from transfusion in patients were used to ascertain the impact of splenectomy. Results: Splenectomy was performed in 56 patients, mainly for non-Hodgkin's lymphoma and myeloproliferative diseases. Median spleen weight was 2·3 (range 1·5–6·0) kg. Mortality at 180 days was zero, and the postoperative complication rate was 25 per cent (17 complications in 14 patients). At 2 years, relief of pain was maintained in 33 of 34 patients, with sustained independence from transfusion in 15 of 19 patients with anaemia and nine of 11 with thrombocytopenia. Spleen weight correlated negatively with BMI ( P = 0·036). Conclusion: Splenectomy for massive splenomegaly is safe and provides effective palliation. Provisional cut-off points relating to spleen size and BMI help to identify patients benefiting from a splenectomy, even those in a critical state. Graphical Abstract: Splenectomy for massive splenomegaly is safe and provides effective palliation. Provisional cut-off points (>2 kg for spleen weight and <24 kg/m 2 for BMI) help to identify patients benefiting from a splenectomy even in a critical state. Safe and very effective